The vaquero in black and other mysterious folktales = El vaquero de negro y otras leyendas misteriosas - Perales, Alonso M. (Alonso Marroquín), 1926- (Arte Público Press, 2015)
Witches, phantoms and other spooky creatures inhabit these stories drawn from Mexican-American folklore. Star-crossed lovers mysteriously disappear; old women metamorphose into wicked owls; phantoms roam the countryside. This ebook edition contains the original Spanish versions along with the author's English translation.